Decomposing productivity and wage effects of intra-establishment labor restructuring - Mika Maliranta; Pekka Ilmakunnas (The Research Institute of the Finnish Economy (ETLA), 2005)
Aggregate productivity growth can be decomposed into growth within establishments, between establishments, and the impact of entering and exiting establishments. We demonstrate that such a productivity decomposition formula can also be used for studying intra-establishment restructuring through the inflow and outflow of workers There are, however, three requirements: Firstly, comprehensive longitudinal linked employer-employee data are needed. Secondly, now the productivity decomposition formula cannot be used for accounting but must be used as an estimation model. Thirdly, the decomposition formula should be such that a meaningful interpretation of its components is possible. The decomposition can also account for different worker types, e.g. age groups. We apply such a method to study the productivity growth and wage growth within the establishments of the Finnish business sector. The results provide empirical evidence on economic incentives for hiring young workers and separating older workers. – – Toimialan tuottavuuden kasvu voidaan dekomponoida toimipaikkojen omaan kasvuun, markkinaosuuksien muutokseen, sekä uusien ja poistuvien toimipaikkojen tuottavuusvaikutukseen. Osoitamme, että samanlaista tuottavuuden dekomponointia voidaan soveltaa myös toimipaikkojen sisäisen rakennemuutoksen tutkimiseen työntekijävirtojen avulla. Tällaisella analyysilla on kuitenkin kolme vaatimusta. Ensiksi, tarvitaan laaja yhdistetty työntekijä-työnantaja-pitkittäisaineisto. Toiseksi, nyt dekomponointimenetelmää ei voida käyttää laskentakaavana vaan estimointiyhtälönä. Kolmanneksi, dekomponointimenetelmän pitää olla sellainen, että sen komponentteja voidaan tulkita mielekkäästi. Dekomponointiin voidaan sisällyttää myös eri työntekijäryhmiä (esim. ikäryhmiä). Käytämme tällaista menetelmää tutkiessamme suomalaisten yrityssektorin toimipaikkojen tuottavuus- ja palkkakehitystä. Tuloksemme antavat empiiristä näyttöä siitä, että yrityksillä on taloudellisia kannustimia palkata nuoria ja irtisanoa vanhempia työntekijöitä.
Keywords: C43; J23; J24; J63; M51; 330; employer-employee data; labor productivity; productivity decomposition; wage determination; worker turnover; työntekijä-työnantaja aineisto; työn tuottavuus; tuottavuus dekomponointi; palkan muodostus; henkilöstön vaihtuvuus; Arbeitsproduktivität; Lohnbildung; Schätzung; Finnland